KONSTRUKSI WACANA KEKERASAN SIMBOLIK TERHADAP POLITIKUS PEREMPUAN INDONESIA DI MEDIA SOSIAL - Ixsir Eliya; Ulfah Mey Lida; Veni Nurpadillah; Muhammad Taufiqurrahman; Wini Ranti (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study explores the forms of language and mechanisms of symbolic violence against Indonesian female politicians on social media. It employs a qualitative approach with a critical linguistics framework by analyzing Instagram comments on the accounts of Puan Maharani, Zita Anjani, Widiyanti Putri Wardhana, and Mulan Jameela. Data were collected through documentation, observation, and note-taking techniques and analyzed from Bourdieu’s perspective. The findings reveal that symbolic violence manifests in three main forms: negative labeling, sexist language, and degrading or dismissive expressions. These practices operate through euphemization and censorship, which normalize violence within public discourse. The study highlights that language on social media functions as an instrument of power that perpetuates patriarchal dominance, undermines women’s professional legitimacy, and potentially hinders their political participation.